Measuring self-directed learning readiness among students of Universiti Teknologi MARA / Norliya Ahmad Kassim - Ahmad Kassim, Norliya (Research Management Institute (RMI), 2008)
The main objective of this study was to examine whether the Universiti Teknologi MARA (UiTM) students were ready to pursue self directing learning as their new learning style. This study applied a quantitative approach using questionnaire as the survey instrument. The instrument was distributed to a sample of 470 final year undergraduate students from Faculty of Information Management (IS), Faculty of Office Management and Technology (OM), and Faculty of Communication and Media Studies (MC) of Universiti Teknologi MARA (UiTM). The total response rate was 87.23% or 410 responses. A combination of descriptive statistics, mean ranking, and one-way analysis of variance (ANOVA), were used to analyze the data. On the average, students perceived themselves to be ready with self directed learning style. The component of Positive Orientation to the Future was the most important in contributing to the readiness in self directed learning. The students of OM were relatively the most ready for the new learning style than students of MC and students of IS and the differences were significant. The findings will be useful to educators and policy makers in universities and those designing Flexible Learning Program for lifelong learning.